PCR cloning and characterization of multiple ADP-glucose pyrophosphorylase cDNAs from tomato - Chen, B Y (Plant science : an international journal of experimental plant biology, 1998)
Four ADP-glucose pyrophosphorylase (AGP) cDNAs were cloned from tomato fruit and leaves by the PCR techniques. Three of them (agp S1, agp S2, and agp S3) encode the large subunit of AGP, the fourth one (agp B) encodes the small subunit. The deduced amino acid sequences of the cDNAs show very high identities (96-98%) to the corresponding potato AGP isoforms, although there are major differences in tissue expression profiles. All four tomato AGP transcripts were detected in fruit and leaves; the predominant ones in fruit are agp B and agp S1, whereas in leaves they are agp B and agp S3. Genomic southern analysis suggests that the four AGP transcripts are encoded by distinct genes